Examining forest economies: A case study of silk value chain analysis in Wajo District - Pratama, Andi Gunawan; Supratman, Supratman; Makkarennu, Makkarennu (Forestry Faculty, Universitas Hasanuddin, 2019)
Value chain analysis is a strategic analytical tool for understanding activities that represent the value of a product (or service), meanwhile providing opportunities for identifying competitive advantage. In this value chain analysis, the research aims to 1) map the actors of silk commodity business ventures, 2) determine the activities of these business actors, and 3) calculate and analyze financial ratios. This study was conducted in the Wajo District as a site historically well known for silk production, and which is undergoing efforts at revival. The method used in this study is observation, interview, and modeling. Data analysis was conducted as a classical value chain analysis, emphasizing the calculations of financial ratios. The results show that the main actors and activities in commodities trading are farmers, local traders, weavers, and silk clothing stores. The largest marketing margin is approximately IDR. 300,000, which is found in silk clothing stores. On the other hand, the smallest marketing margins amounted to about IDR. 100,000, which were identified among local traders. Finally, the largest profit margins were identified among farmers valued at IDR. 196,000, while the smallest profit margins were among local traders amounting to IDR. 68,000. Overall, this case study highlights that forest enterprises, in this case of the silk industry in Wajo, can improve household incomes for forest farmers, while maintaining their overall bargaining position against the market.